Proton-sensing ion channels, GPCRs and calcium signaling regulated by them: implications for cancer - Ji, Renhui; Chang, Li; An, Caiyan; Zhang, Junjing (Frontiers in Cell and Developmental Biology, 2024)
Extracellular acidification of tumors is common. Through proton-sensing ion channels or proton-sensing G protein-coupled receptors (GPCRs), tumor cells sense extracellular acidification to stimulate a variety of intracellular signaling pathways including the calcium signaling, which consequently exerts global impacts on tumor cells. Proton-sensing ion channels, and proton-sensing GPCRs have natural advantages as drug targets of anticancer therapy. However, they and the calcium signaling regulated by them attracted limited attention as potential targets of anticancer drugs. In the present review, we discuss the progress in studies on protonsensing ion channels, and proton-sensing GPCRs, especially emphasizing the effects of calcium signaling activated by them on the characteristics of tumors, including proliferation, migration, invasion, metastasis, drug resistance, angiogenesis. In addition, we review the drugs targeting proton-sensing channels or GPCRs that are currently in clinical trials, as well as the relevant potential drugs for cancer treatments, and discuss their future prospects. The present review aims to elucidate the important role of proton-sensing ion channels, GPCRs and calcium signaling regulated by them in cancer initiation and development. This review will promote the development of drugs targeting proton-sensing channels or GPCRs for cancer treatments, effectively taking their unique advantage as anti-cancer drug targets.